2019
DOI: 10.1515/biol-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic efficacy of thrombelastography (TEG) in patients with preeclampsia and its association with blood coagulation

Abstract: ObjectiveThe aim of this study was to investigate the diagnostic efficacy of thrombelastography (TEG) in patients with preeclampsia.MethodsOne hundred and seventeen pregnant women were recruited from Department of Obstetrics and Gynecology of 1st affiliated Hospital of Fujian Medical University. Of the 117 patients, 59 were normal late gestation (control group), 32 were mild preeclampsia and other 26 cases were severe preeclampsia. All the patients were received thrombelastography (including: K time, Reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…These findings were similar to ours (Figure 1 and Table ), implying coagulation damage that may be related with increased tissue factor and consumption of clotting factors in PE patients 16 . However, according to the study by He et al, 21 the R and K values were found decreased while the MA and α‐angle were increased in PE group, which was consistent with a hypercoagulable state although sampling time was not clearly indicated for PE patients. Therefore, future research with strict sampling window and larger patient cohort is warranted to reveal the dynamic changes of TEG parameters in pregnancies with or without complications.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings were similar to ours (Figure 1 and Table ), implying coagulation damage that may be related with increased tissue factor and consumption of clotting factors in PE patients 16 . However, according to the study by He et al, 21 the R and K values were found decreased while the MA and α‐angle were increased in PE group, which was consistent with a hypercoagulable state although sampling time was not clearly indicated for PE patients. Therefore, future research with strict sampling window and larger patient cohort is warranted to reveal the dynamic changes of TEG parameters in pregnancies with or without complications.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the article by Shupletsova et al reported that the GDM patients experiencing cerebral ischemia (CI) in newborn infants were more likely to present decreased R and K and increased MA and α‐angle than the GDM patients who ended up with no obvious adverse outcomes, implying that glycemia during pregnancy may be involved in programming the development of coagulation disorders and could have effects on TEG results. Unlike GH and GDM, more studies were focused on the direct comparison of TEG parameters between normal and PE pregnancies 16,20,21 . Interestingly, completely opposite changes of TEG parameters were observed in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout pregnancy, the coagulation and fibrinolysis systems maintain a delicate equilibrium, self‐regulating through mutual restriction and promotion 14 . However, as gestational weeks progress, an increase in fibrinogen content and clotting factor levels may lead to a hypercoagulable state 3,15 . While this physiological alteration facilitates placenta detachment during delivery and postpartum recovery, it simultaneously introduces a potential challenge—an imbalance between coagulation and fibrinolysis systems, making the occurrence of thrombosis more likely 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia occurs in approximately 5% of pregnancies and has been investigated in several small studies using POC-VHA, with increases in clot propagation and stabilization observed in severe disease. 67 68 Preeclampsia is complicated by HELLP (Hemolysis, Elevated Liver enzymes, and Low Platelets) syndrome in around 15% of cases where coagulation impairment including thrombocytopenia and hypofibrinogenemia can occur. Abruption is associated with preeclampsia and therefore clotting abnormalities may have mixed causation.…”
Section: Incidence Of Coagulation Abnormalities In Pphmentioning
confidence: 99%